2013
DOI: 10.1103/physrevlett.110.172701
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Multifragmentation Time Scale and Fluctuations of the Largest Fragment Size

Abstract: Distributions of the largest fragment charge, Zmax, in multifragmentation reactions around the Fermi energy can be decomposed into a sum of a Gaussian and a Gumbel distribution, whereas at much higher or lower energies one or the other distribution is asymptotically dominant. We demonstrate the same generic behavior for the largest cluster size in critical aggregation models for small systems, in or out of equilibrium, around the critical point. By analogy with the timedependent irreversible aggregation model,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 82 publications
2
26
0
Order By: Relevance
“…As in [21], it can be seen that Eq. 2 nicely reproduces the non-trivial shapes of these distributions.…”
Section: Iwm Ec 2014 -mentioning
confidence: 53%
See 1 more Smart Citation
“…As in [21], it can be seen that Eq. 2 nicely reproduces the non-trivial shapes of these distributions.…”
Section: Iwm Ec 2014 -mentioning
confidence: 53%
“…Another, indirect, method to gauge the importance of radial flow in multifragmentation reactions was suggested in [21], where it was shown that the Z max distributions in central Xe+Sn collisions evolve with bombarding energy in a manner similar to the largest cluster size distribution in numerical simulations of the Smoluchowski equations for irreversible aggregation in finite systems: for short clusterisation times, s max is an extremal order parameter characterised by the Gumbel distribution; over long timescales s max becomes an additive order parameter characterised by the Gaussian distribution; for intermediate timescales (around the critical gelation time), the s max distribution can be approximated by an admixture of the two asymptotic forms,…”
Section: Iwm Ec 2014 -mentioning
confidence: 99%
“…Moreover the composition of the fit evolves in a regular way from gaussian to gumbellian (R goes from positive to negative values in Fig. 42 By analogy with the irreversible aggregation model the authors of [253] therefore proposed that the exact form of the charge distribution of the largest fragment in nuclear multifragmentation, and hence its fluctuations, are also determined by the timescale of fragment formation in such reactions. The onset and increase of radial expansion at beam energies above 25 MeV per nucleon [87], essential to drive the system towards the onset of spinodal instability and initiation of the break-up into fragments [5], will also effectively shorten the time available for primary fragments to coalesce.…”
Section: Criticality and Correlation Lengthmentioning
confidence: 98%
“…In that case multifragmentation should be an aggregation phenomenon; this was proved by the observation of a universal (Δ)-scaling law of the fluctuations of Z max , which is thus related to an order parameter [7,8].…”
Section: Phase Transition In Finite Systemsmentioning
confidence: 99%